Injectable gelatin–palmitoyl–GDPH hydrogels as bioinks for future cutaneous regeneration: physicochemical characterization and cytotoxicity assessment - Khairul Nizam, Aifa Asyhira; Md Fadilah, Nur Izzah; Ahmad, Haslina; Maarof, Manira; Fauzi, Mh Busra (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Tissue engineering and regenerative medicine have made significant breakthroughs in creating complex three-dimensional (3D) constructs that mimic human tissues. This progress is largely driven by the development of hydrogels, which enable the precise arrangement of biomaterials and cells to form structures resembling native tissues. Gelatin-based bioinks are widely used in wound healing due to their excellent biocompatibility, biodegradability, non-toxicity, and ability to accelerate extracellular matrix formation. However, the role of a novel fatty acid conjugated tetrapeptide, palmitic acid–glycine–aspartic acid–proline–histidine (palmitoyl–GDPH), in enhancing hydrogel performance with human dermal fibroblasts (HDFs) concerning cell survival, proliferation, growth, and metabolism remains poorly understood. This study fabricated gelatin–palmitoyl–GDPH hydrogels at various concentrations (GE_GNP_ELS_PAL12.5 and GE_GNP_ELS_PAL25) using an injectable method and preliminary extrusion-based 3D bioprinting at 24 °C. Physicochemical characterization revealed superior water absorption, biocompatibility, and stability, aligning with optimal wound-healing criteria. In vitro cytotoxicity assays demonstrated >90% cell viability of HDFs cultured on these scaffolds for five days. These results highlight their ability to promote cell survival, proliferation, and adhesion, establishing them as strong contenders for wound healing. This study underscores the potential of gelatin–palmitoyl–GDPH hydrogels as effective bioinks for 3D bioprinting, offering a promising platform for skin tissue engineering and regenerative medicine.